Pengaruh Kompetensi Pengguna, Teknologi Informasi Dan Implementasi SIPD Terhadap Kualitas Laporan Keuangan Pemerintah Daerah Kota Langsa - Yulianda, Devia; Lubis, Nasrul Kahfi; Azhar, Iqlima (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2022)
The purpose of this study is to determine the effect of user competence, information technology and SIPD implementation on the quality of Langsa City government financial reports. The sample in this research is 60 respondents. Methods of data analysis using multiple linear regression analysis, t test, F test, and analysis of the coefficient of determination. The regression equation in this study is Y = 3.270 +0.197X1 + 0.157 X2 + 0.588X3. User competence has a positive and significant effect on the quality of the Langsa Municipal government's financial reports, where the t test obtains a sig t value. 0.027 <0.05. Information technology has a positive and significant effect on the quality of the Langsa Municipal government's financial reports, where the t test obtains a sig t value. 0.035 <0.05. The implementation of SIPD has a positive and significant effect on the quality of the financial reports of the Langsa City government, where the t test obtains a sig t value. 0.022 <0.05. User competence, information technology and SIPD implementation simultaneously have a positive and significant effect on the quality of the Langsa Municipal government's financial reports, where the F test obtained a sig F value. 0.000 < 0.05. From the test of the coefficient of determination it is known that user competence, information technology and SIPD implementation affect the quality of the Langsa Municipal government's financial reports by 51.7%, while the remaining 48.3% is influenced by other variables outside this research model.